Analisis Pelanggaran Strategi Pemasaran Industri Hiburan di Media Sosial - Aisyah Yulia Citra; Halimah Zahrah; Fahdah Athifah Haura Fadhilah; Fahra Awalia Zahra (Teewan Journal Solutions, 2025)
This study discusses violations of marketing strategies in the entertainment industry through social media that have a negative impact on the reputation and trust of the audience. This study aims to analyze the types of violations that occur, their main causes, and their impact on the company's image. This study uses a qualitative method with a literature study approach that refers to 14 academic references including national journals, international journals, and theory books. The results of the study indicate that violations such as content manipulation, exploitation of sensitive issues, and misuse of personal data are very detrimental to entertainment companies in the long term. Therefore, this study recommends that companies implement more ethical and transparent marketing strategies in utilizing social media.